FENOMENA JOSHI KOSEI DALAM KEHIDUPAN MASYARAKAT JEPANG - Budi Mulyadi (Diponegoro University, 2018)
(Title: Joshi Kosei in The Life of Japanese Society). The main goal of this research is to know about Joshi Kosei (A Teenager Prostitution) in The Life of Japanese Society. This research is a combination between field and library reserach. Main method are observation, interview, interpretation. The research show the history of prostitution in Japan, the factors, and the effects for teenagers who are doing the job. The law in Japan has taken prostitution as a legal job, but it engenders a social problem especially a prostitution that involved teenagers. For Japanese people prostitution is not something taboo, it becomes a bussiness which is developed really fast in JapanKeywords : Joshi Kosei; Prostitution; Japanese Society